KERAGAMAN BAKTERI PENGHASIL ENZIM PENGHIDROLISIS NITRIL DI PULAU ENGGANO BENGKULU [Diversity of Nitrilase Producing Bacteria in Enggano Island, Bengkulu] - Riffiani, Rini; Sulistinah, Nunik (BERITA BIOLOGI, 2017)
Potential nitrile degrading microbes have been isolated from marine sponge, marine water and soil in Enggano Island. Nitrilase enzyme has a function in degrading nitrile compund. Nitrilases are important industrial enzymes because of their ability to produce biologically active to degrade enantiomers, such as S-(+)-1-(4â-isobutylphenyl) propionic acid (S-(+)-ibuprofen) and R-(-) mandelic acid. Mandelic acids, which are important as pharmaceutical intermediates, can be produced in enantiomerically pure form by the hydrolysis of their corresponding nitrile. The aim of the study was to explore the diversity of nitrile degrading bacteria in Enggano Island, and their ability to utilize nitrile as a substrate growth. Screening of such microbes were carried out by using microtitter plate method based on growth ability tested by INT (Iodonitrotetrazoliumchloride). Degradation product was determined by High Performance Liquid Chromatography (HPLC). Seventy nine bacteria were able to grow on acetamide, acetonitrile, benzonitrile, adiponitrile, mandelonitrile, succinonitrile, lactonitrile, dan benzilcyanide as the sole source of carbon and nitrogen. Two isolates, YIM 56238 and PO69, have shown to enantioselectively hydrolyze racemic mandelonitrile to mandelic acid. Based on 16S rRNA gene identification, these bacteria have the highest sequence similarity to Microccous endophyticus strain YIM 56238 and Rhodococcus pyridinivorans strain PO69.